Age-specific dynamics of physical working capacity and functionality at female rowers' training process stages - Abramova, T. F.; Nikitina, T. M.; Yakutovich, N. M. (Theory and Practice of Physical Culture, 2017)
Abstract: Competitive success in modern sports is often largely limited by the training loads being prematurely intensified with poor if any consideration for the core energy systems growth and development logics. The study was designed to analyse the age-specific variations of body build, working capacity and energy supply rates in 80 subject female rowers of 16-35 years of age in the sport excellence to the top athletic mastery training period. The following methods were applied in the study: anthropometrics, callipering, biochemical analysis of blood, functionality tests (physical working capacity, external respiration rating tests), and heart rate measurements. The study data and analyses gave the means to find the morphological and functional state development and physical working capacity formation logics in female rowers in every sport excellence stage. The study findings showed the traditional physical development and training chronology - with the new regionally trained athletes being prematurely included in the teams - forming a gap in succession and development of the strength and regulatory aspects of the athletic physical resources.